Short Communication: Antioxidant activity and metabolite profiles of leaves and stem extracts of Vitex negundo - MUHAMMAD ALFARABI; TURHADI TURHADI; TRINI SURYOWATI; NURIN AYU IMANELI; PRETTY OKTAVIANI SIHOMBING (Society for Indonesian Biodiversity, 2022)
Abstract. Alfarabi M, Turhadi, Suryowati T, Imaneli NA, Sihombing PO. 2022. Short Communication: Antioxidant activity and metabolite profiles of leaves and stem extracts of Vitex negundo. Biodiversitas 23: 2663-2667. Many plantspecies could be used as natural sources of antioxidants, one of which is Vitex negundo or lagundi which grows widely in Southeast and South Asia. Due to the wide distribution of growth areas, so different habitats could be a factor causing variations in V. negundo bioactivity, especially antioxidant activity. In addition to environmental factors, extract derived from different plant parts could also contribute to variations in the content of metabolites that affect bioactivity. The objective of this study was to determine the antioxidant activity of leaf and stem extracts of V. negundo and evaluate the metabolites contained in the extracts. Antioxidant activity analysis was performed using the free radical 2,2-diphenyl-1-picrylhydrazyl (DPPH), and GC-MS analysis was used to identify bioactive metabolites. Leafand stem extract of V. negundo showed antioxidant activity directly proportional to the increasein extract concentration. A total of 8 metabolites were identified from the three extracts, i.e., acrolein, hydroquinone, sitosterol, naphthalene, pyrogallol, squalene, phytol, and hexadecenoic acid. There were correlations between antioxidant activity and the metabolites contained in the three extracts. It is suggested that the bioactivity of the extract is due to the interaction of these metabolites.